Perbedaan Frekuensi PVA (Patient Ventilator Asynchrony) Pada Beberapa Level Sedasi Pasien Kritis - Ridwan, Romi; Suwarman, Suwarman; Kestriani, Nurita Dian Kestriani Dian (Faculty of Medicine, Universitas Padjadjaran, 2025)
Background: Patient–ventilator asynchrony (PVA) is a frequent but often underrecognized phenomenon in mechanically ventilated patients, associated with adverse outcomes. Sedation depth is a modifiable factor affecting PVA, yet data from resource-limited ICUs remain scarce. This study aimed to evaluate PVA prevalence and its association with sedation depth and mechanical ventilation duration.Methods: A cross-sectional observational study included 60 adult ICU patients on mechanical ventilation. Ventilator waveform recordings were analyzed over 30-minute periods, totaling 41,372 breaths. PVA events were identified, classified, and quantified. Sedation depth was categorized as fully awake, light sedation, or deep sedation. Associations between sedation depth, PVA frequency, and mechanical ventilation duration were assessed using statistical tests.Results: A total of 2,539 PVA events were detected, yielding an overall asynchrony rate of 6.1%. Ineffective effort was most common (58%), followed by double triggering (17.2%) and flow asynchrony (15.3%). Mean PVA values increased significantly with deeper sedation (p<0.05). A weak but statistically significant positive correlation existed between average PVA and duration of mechanical ventilation (r=0.306, p<0.05).Discussion: PVA is prevalent in mechanically ventilated ICU patients, with ineffective effort predominating. Deeper sedation levels are associated with higher PVA frequency, which correlates with prolonged ventilation. These findings emphasize the need for careful sedation management and routine ventilator waveform monitoring to improve patient–ventilator interaction.Conclusion: Patient–ventilator asynchrony is common and significantly associated with sedation depth and ventilation duration. Optimized sedation and vigilant waveform monitoring may enhance synchrony and reduce ventilation time